Network slicing scheme for heterogeneous power wireless communication networks - Yan ZHEN; Mengyue YU; Haibo ZHAO (Dianxin kexue)
Targeted at power communication networks,the concepts of vertical and horizontal slicing was introduced,the slicing enabler technologies,then explain the technial challenges of realizing network slicing in power communication networks,finally a slicing scheme for heterogeneous power wireless communication networks was proposed in which vertical slicing guarantees specific applications’ quality and horizontal slicing improves efficiency and flexibility of system entities and terminal devices.